PENENTUAN KRITERIA DALAM PEMILIHAN JENIS PERKERASAN PADA DATARAN TINGGI DI KABUPATEN TRENGGALEK - Anang Prayogo; Hitapriya Suprayitno; Herry Budianto (Journal of Civil Engineering, 2018)
Road infrastructure at hilly area is highly needed and very important to support the economics stability in the district of Trenggalek. Road infrastructure becoming the most important nowadays for the people of Trenggalek especially for those who live in the highland. The problems recently happened until now is the road infrastructure in the district of Trenggalek especially in the highland are many damaged, not feasible and many more that requires to be restored. The type selection of the pavement that proper and suit for the highland in the district of Trenggalek is highly influenced by some criteria. And from some literature study we can draw conclusions in 6 (six) criteria those are, road user safety, road user amenities, cost of construction, ease of execution for the road construction, treatment of the road construction after the maintenance period expired and the availability of the materials. Then from interviewing the respondents that has experienced in the road construction especially in the highland of Trenggalek concluded 7 (seven) criteria those are, road user safety, road user amenities, cost of construction, situation and condition of the project location, treatment of the road construction after the maintenance period expired and the durability to the scouring water.